2020
DOI: 10.1371/journal.pone.0237329
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality among Chinese college students: A cross-sectional study across seven provinces

Abstract: Background Although the suicide rate in China has decreased over the past 20 years, there have been reports that the younger age group has been experiencing an increased incidence of completed suicide. Given that undergraduate groups are at higher risks of suicidality, it is important to monitor and screen for risk factors for suicidal ideation and behaviors to ensure their well-being. Objective To examine the risk and protective factors contributing to suicidality among undergraduate college students in seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
2
14
0
4
Order By: Relevance
“…Previous studies also indicated that the prevalence of suicidal ideation in the middle-aged and elderly group was associated with loneliness, household financial problems, and poor perceived health [ 84 , 85 ]. This study also revealed that the prevalence of suicidal ideation was higher in people from only-child families, which was consistent with a previous result [ 86 ]. Experts explained that elderly people from rural areas, with a lack of pension provision and children, generally had a sense of responsibility to their parents, which resulted in an increase in the stress of life as an only child [ 87 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies also indicated that the prevalence of suicidal ideation in the middle-aged and elderly group was associated with loneliness, household financial problems, and poor perceived health [ 84 , 85 ]. This study also revealed that the prevalence of suicidal ideation was higher in people from only-child families, which was consistent with a previous result [ 86 ]. Experts explained that elderly people from rural areas, with a lack of pension provision and children, generally had a sense of responsibility to their parents, which resulted in an increase in the stress of life as an only child [ 87 ].…”
Section: Discussionsupporting
confidence: 93%
“…The measures consisted of sociodemographic information, selfharm, suicidal behaviour and social withdrawal behaviour, and were used to examine the association between prolonged social withdrawal behaviour and self-harm and suicidal behaviour. We also included the psychological protective factors and mental health-related risk factors, which were adopted in recent research of suicidality among Chinese university students, 22,23 to further examine the association after controlling relevant protective and risks factors.…”
Section: Instrumentsmentioning
confidence: 99%
“…The SBQ-R, developed by Osman et al (2001) has four items for evaluating previous and future suicidal thoughts and behaviors: the presence and frequency of previous of suicidal ideation and attempts, communication of suicidal thoughts to others, and how likely is a future suicidal attempt. The SBQ-R has shown high internal consistency in various samples (e.g., Aloba et al, 2017; Amini-Tehrani et al, 2020; Glaesmer et al, 2018; Gómez-Romero et al, 2021; Lew et al, 2020; Osman et al, 2001). In the present study, the intention to die was assessed by the SBQ-R.…”
Section: Methodsmentioning
confidence: 99%